Experimental Investigations on Cement Concrete by Using Different Steel Waste as a Fibre to Strengthen the M40 Concrete - Kuldeep Kumar Yadav; Er. Vikram (IJRDO - Journal of Mechanical And Civil Engineering, 2019)
As the human going to grow in technology enhances not only human comforts but also damages the environment. Use of metals as containers has become popular and safe now, especially to carry the liquids. Inspite of the inherent advantages and disadvantages existent in its disposal. Today the construction industry is in need of finding cost effective materials for increasing the strength of concrete structures. Hence an attempt has been made in the present investigations to study the influence of addition of waste materials like lathe waste, soft drink bottle caps, empty waste tin, waste steel powder from workshop at a dosage of approximate 0 To 1.6% of total weight of concrete as a fiber. The lathe waste, empty tins, soft drink bottle cops were deformed into the rectangular strips of 15mm to 25mm in size. Green building is an increasingly important global concern and a critical way to conserve natural resources and reduce the amount of materials going to our landfills. Large quantities of metal waste are generated from empty metal cans and bottle caps of juices and soft drinks. This is an environmental issue as metal waste is difficult to biodegrade and involves processes either to recycle or reuse. In this investigation, a comparison have been made between plain cement concrete and the fiber reinforced concrete containing lathe scrap (steel scrap)in various proportions by weight. The fiber used is irregular in shape and with varying aspect ratio. The 28 days strength of WSFRC for compressive strength, tensile strength and flexural strength is found to be increased when compared with the 28 days strength of plain cement concrete. Experimental investigation has been done by using M40 mix and tests has carried out as per recommended procedure by with conventional concrete has been gain more tensile strength as well as compressive strength .concrete is weak in tensile strength and strong in compression so while we improve the tensile strength.